Simulating the damage extent of unreinforced brick masonry buildings under boulder impact using three-dimensional discontinuous deformation analysis (3-D DDA). (November 2018) - Li, Zhujun; Liu, Shuguang; Zhang, Hong; Chen, Guangqi; Wu, Wei; Zhu, Hehua; Zhuang, Xiaoying; Wang, Wei
Abstract: The main material of brick masonry buildings is discontinuous masonry material. This study presents a critical review of the damage characteristics of masonry and the methods for studying the behavior of masonry. The damage extent of brick masonry buildings under boulder impact is analyzed using an approach based on three-dimensional discontinuous deformation analysis (3-D DDA). A "block-joint" model is established to represent the brick and mortar of the building, which is based on the discontinuous characteristics of the masonry material. On this basis, a benchmark model is used to validate the 3-D DDA. Using this approach, the velocity distribution and several displacements of key points of the building blocks are obtained to compare the damage extent of the building under six different cases that consider in-plane or out-of-plane boulder impacts to the building at different heights. The size and material parameters of the building model are based on the most common buildings in the field of investigation. These results can be used to show the failure process of buildings on a continuous basis or to quantitatively compare the damage extent of different types of buildings. By analyzing the force condition of the basic element blocks, the results demonstrate that the damage extent of the building is related to the impact direction, impact height, location relationship between the damaged part and the impact position, and constraint condition. Highlights: Kinetic damage analysis of brick masonry buildings with different impact direction and height Damage characteristics: velocity distribution and key displacements of blocks Consistency of numerical solutions with analytic solutions in the impact effect Correct numerical solutions of damage extent consistent with force analysis